Analisis Kinerja Keuangan Pada Bank Perkreditan Rakyat (BPR) di Kabupaten Magelang - Anindya Rifka Utami; Agustina Prativi Nugraheni (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
The study aims to determine the financial performance of rural banks in the Magelang district based on aspects of minimum capital adequacy, asset quality, profitability and liquidity. The data collection techniques used are secondary data techniques and the documentation of financial statements. The data analysis method used is the descriptive method. The results of this study show that the state of the annual financial statements of BPRs in the Magelang Regency area has not yet been able to meet Bank Indonesia's 5 ratio standard, which can be described as healthy.